2015
DOI: 10.1038/srep11421
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of silymarin against chikungunya virus

Abstract: The mosquito-borne chikungunya virus (CHIKV) causes chikungunya fever, with clinical presentations such as severe back and small joint pain, and debilitating arthritis associated with crippling pains that persist for weeks and even years. Although there are several studies to evaluate the efficacy of drugs against CHIKV, the treatment for chikungunya fever is mainly symptom-based and no effective licensed vaccine or antiviral are available. Here, we investigated the antiviral activity of three types of flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
93
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 26 publications
0
93
1
Order By: Relevance
“…Quercetin 3-␤-O-D-glucoside (Q3G), for example, is a natural derivative of quercetin that contains a glucoside molecule, and this has been shown to enhance the solubility and bioavailability of the compound when ingested (16). Although much research on quercetin and its derivatives has focused on their properties as potential therapeutic agents against cancer and inflammatory diseases and their anti-metabolic disease effects (17), recent studies have also demonstrated antiviral activity against a wide variety of viruses, including influenza virus, Chikungunya virus, Epstein-Barr virus, hepatitis C virus, and Mayaro virus (18)(19)(20)(21)(22). While a detailed mechanism of action remains undefined, it has been proposed that quercetin and its derivatives affect a step in the viral entry process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin 3-␤-O-D-glucoside (Q3G), for example, is a natural derivative of quercetin that contains a glucoside molecule, and this has been shown to enhance the solubility and bioavailability of the compound when ingested (16). Although much research on quercetin and its derivatives has focused on their properties as potential therapeutic agents against cancer and inflammatory diseases and their anti-metabolic disease effects (17), recent studies have also demonstrated antiviral activity against a wide variety of viruses, including influenza virus, Chikungunya virus, Epstein-Barr virus, hepatitis C virus, and Mayaro virus (18)(19)(20)(21)(22). While a detailed mechanism of action remains undefined, it has been proposed that quercetin and its derivatives affect a step in the viral entry process.…”
mentioning
confidence: 99%
“…(Fig. 1A) is a glucosylated form of quercetin, a flavonoid compound that has been shown to exhibit antiviral activity against several RNA viruses (18)(19)(20). In order to test the antiviral activity of our compound against ebolavirus, we first calculated the EC 50 and EC 90 values using Vero E6 epithelial cells.…”
mentioning
confidence: 99%
“…Targeting of several metabolic pathways has revealed anti-CHIKV effects of several licensed drugs (3). Compounds most likely targeting virus entry or host cell-specific components required for virus infection have been described (4)(5)(6)(7)(8). Several nucleosides or nucleotides, acting as pseudosubstrates for CHIKV RNA-dependent RNA polymerase and/or using another, more general mechanism of action, have shown anti-CHIKV activity (9).…”
mentioning
confidence: 99%
“…This inhibition appeared to be more potent than that of the control nucleoside analogs favipiravir and ribavirin, previously described to have anti-CHIKV activity (12,17). A continuous-treatment assay was conducted to evaluate the antiviral activity of the compound against infectious CHIKV replication in Vero cells (18). Briefly, monolayers of Vero cells were treated with different concentrations of the compound, starting from the maximum nontoxic dose.…”
mentioning
confidence: 99%